Prevalence of Hypocalcemic Fits in Exclusively Breast Fed Infants - Arzoo Idrees, Manzoor Ali Khan, Mohsna Saeed Zia, Syed Zakir Hussain Shah, Ishtiaq Ahmed Mughal, Khawaja Abrar Ahmed (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the prevalence of hypocalcemia fits in exclusively breast fed infants. Study design: Prospective study. Place and duration of study: Department of Paediatric Medicine, Abbas Institute of Medical Sciences/Medical College Muzafarabad AJ Kashmir from 01-04-2021 to 31-03-2022. Methodology: One hundred breast fed infants were enrolled. A 0.5cc blood of child was withdrawn for conductance of serum calcium and 25(OH) vitamin D3 test while 2cc of mother blood was also withdrawn for analyzing their calcium levels as well as vitamin D status in duplicate batches. Radiological imaging through x ray image of wrist for detection of rickets was performed in each infant. Infants having complain of fits were specifically observed fit/seizure time duration of the fit, the time when it occurred, eye rotation and cyanosis condition. Any family history regarding epilepsy especially in mothers was also noted. Results: The mean age of the infants was 5.5±2.3 months with a range of 1-12 months. Majority of the infants were male gender with a parentage of 66% while there were 34% female gender infants. Within the total number of infants included 30 children were having clinically defined rickets with 25 such infants who were having vitamin D level below the level of 20ng/ml. Conclusion: There is a low prevalence of hypocalcemia fit among breast fed infants.